Quantitative Histomorphometrical Analysis in Distinguishing Non-Hodgkin Malignant Lymphoma, Large Cell Type with Nasopharyngeal Carcinoma - Husain, Okky; Aminah Usman, Hermin; Yantisetiasti, Anglita; Handayani, Astri; S Hernowo, Bethy (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Non-Hodgkin’s Malignant Lymphomas (NHMLs) with large cell morphology have similar histopathological appearance with Nasopharyngeal Carcinoma, undifferentiated type therefore ancillary examination such as Immunohistochemistry (IHC) are required. Quantitative histomorphometrical analysis able to identify subtle detail. The aim of this study is to measure the accuracy of quantitative histomorphometrical analysis to distinguishing NHML, large cell type with Nasopharyngeal Carcinoma. Methods Up to 33 Hematoxylin and Eosin (HE) slides from NHML, large cell type, and 27 cases of Nasopharyngeal Carcinoma were photographed under 400 times magnification with a total of 7131 images. Background, nuclei, and extra-nuclear components between cells are segmented as mathematical objects. Objects’ properties were measured and represented as distribution factors (minimum, quartile 1, median, quartile 3, maximum, range, and interquartile range). Significant factors that can differentiate the study groups are measured with a fisher-exact statistical test. Models to predict NHML, large cell type from nasopharyngeal carcinoma were formulated with different numbers of factors. The HE diagnosis accuracy compared to IHC was measured Results A sum of 7131 with 3893 from NHMLs, large cell type, and 3238 images of nasopharyngeal carcinoma were collected. After features selection, up to 76 properties factors are selected. Models' accuracy are ranging from 72.67% with a single factor and up to 89.9% with the whole selected factors. Summary Models’ accuracy are higher (72.6-89.9%) compared to HE primary diagnosis (60%) in distinguishing NHML, large cell againts nasopharyngeal carcinoma. Quantitative histomorphometry can assist pathologist for early screening to distinguishing NHML, large cell type with Nasopharyngeal Carcinoma.